Persepsi masyarakat terhadap pelayan publik PT. PLN Rayon Taniwel - Beatus Mendelson Laka; Amelia Niwele (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
Perception is a person's perspective on an object that is seen, be it people, goods or companies. Public perception of public servant PT. PLN Rayon Taniwel is a good thing for the better service to electricity customers. Therefore, the writer is very interested to examine this problem because during this service PT. PLN Rayon Taniwel is bad in the eyes of society. The purpose of this research for PT. PLN Rayon Taniwel can improve the good service for its customers. The results of this study also shows that during this time the customers of PT. PLN Rayon Taniwel is not satisfied with the services provided. Caused by regular account payments every month but their rights as customers do not enjoy lighting well. Even the lighting done by PLN to the customer is very unusual.DOI: https://doi.org/10.26905/pjiap.v4i2.2271